Dinamika Strategi Penetapan Harga Terhadap Permintaan Konsumen Di Marketplace : Systematic Literature Riview Dalam Ekonomi Manajerial - Enjelia, Meebya; ., Supriyanto (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
The rapid growth of digital marketplaces has increased the complexity of pricing strategies and consumer demand behavior. In a highly transparent and competitive environment, pricing plays a crucial role in shaping purchasing decisions. This study aims to identify pricing strategies, analyze their impact on consumer demand, and examine research gaps from a managerial economics perspective. A Systematic Literature Review (SLR) method with a PRISMA approach was applied, involving identification, screening, evaluation, and synthesis stages. A total of 10 key articles from various databases were selected for in-depth analysis. The findings reveal a shift from cost-based pricing toward more adaptive approaches, such as value-based pricing, competition-based pricing, and dynamic pricing. These strategies significantly influence consumer demand, which is affected by price elasticity, perceived value, product quality, and digital market conditions. Behavioral and technological factors further intensify these dynamics. Additionally, the study highlights several research gaps, particularly the limited empirical evidence, insufficient integration of technology, and concerns related to price fairness and non-economic factors. Therefore, pricing strategies should be designed in a data-driven and adaptive manner to effectively stimulate consumer demand in digital marketplaces.